From Sectarian Labels to Universal Ethics: Human Deviance in Abrahamic Scriptures - Satrio Nurbantara; Muhamad Iqzman Addif Su’aidi (Basmala: Journal of Qur’an and Hadith, 2025)
Research concerning the theme of human misguidance within the Qurʾān, the Tanakh, and the Gospel has predominantly evolved within the distinct hermeneutical frameworks intrinsic to each tradition. This approach often yields sectarian interpretations that employ the concept of misguidance as a marker of theological identity. A significant gap in the scholarship persists due to the paucity of comparative studies that integrate philological analysis with ethical reflection across these sacred texts. This article seeks to address this lacuna by investigating the concept of human misguidance across the three Abrahamic traditions as a universal ethical typology, employing Paul Ricoeur’s narrative-hermeneutical methodology. The analysis focuses on the expressions al-maghḍūb and al-ḍāllīn in Sūrat al-Fātiḥah, the notion of qĕshēh ʿōref (“stiff-necked people”) in the Tanakh, and the parable of the Lost Sheep in the Gospel. Utilizing Ricoeur’s three-stage mimesis framework—prefiguration, configuration, and refiguration—this study examines the linguistic and historical contexts of each concept, synthesizes them into a coherent comparative interpretive structure, and recontextualizes them within a contemporary ethical framework. The findings demonstrate that, despite linguistic and theological divergences, the three Abrahamic traditions conceptualize misguidance as an anthropological condition characterized by conscious rebellion against truth, hardness of heart, and existential loss arising from human ignorance or vulnerability. This article argues that misguidance is more accurately understood as a universal moral category rather than a sectarian designation. Theoretically, these findings contribute to the field of comparative Qurʾanic hermeneutics, while practically they offer an ethical–theological foundation for fostering interfaith dialogue in contemporary pluralistic contexts. [Kajian tentang kesesatan manusia dalam Al-Qur’an, Tanakh, dan Injil selama ini cenderung berkembang dalam kerangka tafsir internal masing-masing tradisi dan kerap terjebak dalam pembacaan sektarian yang menempatkan konsep kesesatan sebagai penanda identitas teologis. Minimnya kajian komparatif lintas kitab suci yang mengintegrasikan analisis filologis dan refleksi etis menunjukkan adanya celah penelitian yang signifikan. Artikel ini bertujuan mengkaji konsep kesesatan manusia dalam tiga tradisi Abrahamik sebagai tipologi etis universal melalui pendekatan hermeneutika naratif Paul Ricoeur. Penelitian ini memfokuskan analisis pada istilah al-maghdūb dan aḍ-ḍāllīn dalam Surah al-Fātiḥah, konsep qesheh ‘ōref (orang yang keras kepala) dalam Tanakh, serta perumpamaan lost sheep dalam Injil. Dengan menggunakan kerangka tiga tahap mimesis—prafigurasional, konfiguratif, dan refigurasional—studi ini menelusuri horizon linguistik dan historis masing-masing konsep, mensintesiskannya dalam satu struktur makna komparatif, serta merefigurasikannya dalam konteks etis kontemporer. Hasil penelitian menunjukkan bahwa meskipun berbeda dalam bahasa dan aksentuasi teologis, ketiga tradisi Abrahamik merepresentasikan kesesatan sebagai pengalaman antropologis yang mencakup pembangkangan sadar terhadap kebenaran, ketertutupan hati, dan keterhilangan akibat kebodohan atau kerapuhan manusia. Artikel ini berargumen bahwa konsep kesesatan lebih tepat dipahami sebagai kategori moral universal daripada label sektarian. Secara teoretis, temuan ini memperkaya hermeneutika komparatif Al-Qur’an, sementara secara praktis ia menawarkan landasan etis-teologis bagi penguatan dialog antaragama dalam konteks pluralisme kontemporer.]